2023
DOI: 10.3390/ijerph20064758
|View full text |Cite
|
Sign up to set email alerts
|

Health System Factors Affecting the Experience of Non-Invasive Ventilation Provision of People with Neuromuscular Disorders in New Zealand

Abstract: Non-invasive ventilation (NIV) is a critical therapy for many patients with neuromuscular disorders (NMD), supporting those with respiratory failure to achieve adequate respiration and improve their quality of life. The aim of this study was to explore the experiences of access to, consent, uptake, maintenance and safe use of non-invasive ventilation by people with NMD. Semi-structured individual interviews were conducted with 11 people with NMD, each using NIV for more than 12 months. A critical realism ontol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…People with neurological and complex health conditions are at greatest risk of poor transitions between health services 21 . Participants confirmed previous reports that differences in care were worse for people in rural areas, 10,15,22 but made no specific references to differences by ethnic background.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…People with neurological and complex health conditions are at greatest risk of poor transitions between health services 21 . Participants confirmed previous reports that differences in care were worse for people in rural areas, 10,15,22 but made no specific references to differences by ethnic background.…”
Section: Discussionmentioning
confidence: 51%
“…We found that clinicians are concerned about differences in the access to and quality of non‐invasive ventilation services. Our companion study of the experiences of people with neuromuscular disorders found that they reported similar health system, organisational, and health professional factors affecting non‐invasive ventilation services 15 …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations